Immunotherapy treatments for small-cell lung cancer: past, present and future - Whitehurst, Matthew (Lung Cancer Manag, 2013)
Small-cell lung cancer remains a considerable cause of morbidity and mortality. To this day, first-line therapy continues to be a platinum agent with etoposide, combined with radiation therapy in cases of limited stage disease. Numerous, largely unsuccessful, attempts at controlling the disease have included different chemotherapy strategies, the utilization of antiangiogenic agents, tyrosine kinase inhibitors, mammalian target of rapamycin inhibitors and other treatment modalities. Immunotherapy, including vaccines, immune response modifiers, inhibitors of check point blockades and immunologic-targeted toxins may well be the future of treatment, not only to enhance the proven chemotherapy effects, but to improve the control of minimal residual disease and the response with salvage chemotherapy. This article reviews the current advances in immunotherapeutic strategies against small-cell lung cancer.